2021
DOI: 10.5551/jat.54064
|View full text |Cite
|
Sign up to set email alerts
|

Serum High-Sensitivity C-Reactive Protein Levels and the Risk of Atrial Fibrillation in Japanese Population: the Circulatory Risk in Communities Study

Abstract: Aim: This study aimed to investigate the association between the serum high-sensitivity C-reactive protein (hs-CRP) levels and incident atrial fibrillation risk in the general Japanese population, who have lower hs-CRP levels than the Western population, and assess whether the association is modified by sex, overweight, hypertension, and smoking status. Methods: We conducted a prospective study in 6517 Japanese men and women aged 40–79 years without atrial fibrillation at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…A similar association was also reported by another population-based cohort study in Japan, recently. 24 In addition, the present study showed that the subjects with a persistently high serum hs-CRP level showed an approximately values both in 1988 and in 2002). In contrast, the "decreased" subgroup (i.e., subjects in whom serum hs-CRP levels were higher than the cut-off values in 1988 but lower in 2002) was not associated with a risk of AF.…”
Section: Resultssupporting
confidence: 55%
“…A similar association was also reported by another population-based cohort study in Japan, recently. 24 In addition, the present study showed that the subjects with a persistently high serum hs-CRP level showed an approximately values both in 1988 and in 2002). In contrast, the "decreased" subgroup (i.e., subjects in whom serum hs-CRP levels were higher than the cut-off values in 1988 but lower in 2002) was not associated with a risk of AF.…”
Section: Resultssupporting
confidence: 55%
“…Moreover, the most prominent risk factors for AF development, such as age, sex, increased BMI, hypertension, and HF, have all been related to elevated natriuretic peptide concentrations. Previous studies showed that patients with AF had signifcantly higher CRP levels than the SR group [20], and elevated hs-CRP levels were signifcantly associated with an increased risk of AF [35][36][37]. However, circulating BNP and CRP are known biomarkers for systemic circulation and can be infuenced by many factors, such as HF and acute or chronic infammation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have noted an association between leukocyte counts and AF ( 30 ). However, more studies focus on CRP as a primary predictor of NOAF ( 31 , 32 ). CRP could act on monocytes/macrophages, vascular endothelial cells, and smooth muscle cells to secrete pro-inflammatory molecules to induce cardiovascular disease ( 33 ).…”
Section: Discussionmentioning
confidence: 99%